1995
DOI: 10.1038/sc.1995.72
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of spinal cord injuries in Novosibirsk, Russia

Abstract: The incidence of spinal cord injuries (SCI) in Novosibirsk is 29.7 per million per year. Almost all of these SCI patients (94,3%) are hospitalized to our clinic. Over the past 5 years (since 1989), a total of 196 patients with SCI were admitted, SCI were distributed as follows: cervical, 96 patients (49.0%); thoracic, 54 (27.5%); and lumbar, 46 (23,5%). SCI was diagnosed using computed tomography (CT), magnetic resonance imaging (MRI), pneumomyelography, epidurography, radiography and electrophysiological meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 6 publications
2
30
0
7
Order By: Relevance
“…New Estonian data are combined with regional data for Russia [41][42][43] and show the main causes of TSCI in Estonia and Russia (Novosibirski and Saint Petersburg) were falls (median 40%) and land transport (median 25%). values were calculated from information contained in Supplementary Table 3.…”
Section: Europe Easternmentioning
confidence: 99%
“…New Estonian data are combined with regional data for Russia [41][42][43] and show the main causes of TSCI in Estonia and Russia (Novosibirski and Saint Petersburg) were falls (median 40%) and land transport (median 25%). values were calculated from information contained in Supplementary Table 3.…”
Section: Europe Easternmentioning
confidence: 99%
“…Otom et al 8 reported that the incidence rates for traumatic spinal cord injury (TSCI) of 18 per million populations in Jordan, from January 1988 to December 1993. In Russia, 9 this rate was 29.7 per million per year between 1989 and 1994.…”
Section: Introductionmentioning
confidence: 97%
“…The mean age is lower in Iran (31 years), Russia (34.2 years) and Jordan (33 years). 5,14,19 The younger average age of TSCI patients in developing countries is related to the large number of young people working in the industrial economy and inherent habits and lifestyles. For example, young people usually sleep on rooftops during hot summers in Turkey, and young people climb trees to pick fruit in South Asia.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13] However, falling was the primary injury cause of TSCI in developing countries, such as Russia, Pakistan, Nepal and some portions of southern Asia. [14][15][16] Similar to other developing countries, the top three causes of TSCI in the hospitalized patients in Beijing (according to a sampling survey conducted in 2002) were falling from a height (37.5%), transportation accidents (26.9%) and being struck by an object (16.3%). 8 In the present study, 561 TSCI patients whose injuries occurred between 2001 and 2010 were recruited.…”
Section: Introductionmentioning
confidence: 99%